İngilizce Öğretmeni Adaylarının Konuşma Kaygılarını Azaltmak İçin Tasarlanmış Bir Eylem Araştırması - Uysal, Derya; Gökçe, Sevgi (Bartın Üniversitesi, 2024)
This present study was driven by the need to help the first-grade English language teacher candidates control high foreign language speaking anxiety. A 14-week action plan was designed to alleviate negative feelings the teacher candidates experienced during the course of “Oral Communication Skills-I” and improve their speaking performance. In order to identify the learners' problems and their development before and after action, multiple sources of data were collected by means of quantitative and qualitative measures. Regarding the results, the participants reported positive effect of the action on their speaking skill, interpersonal skills and self-confidence. Also, a slight decline in their speaking anxiety was revealed. On the other hand, a decline in their speaking performance was observed. Thus, the action was useful in supporting social and psychological factors that influence improvement of speaking skill in a positive way. Last, the results gave evidence on the need for similar actions that allow teacher candidates to use English for communicative purposes.
An Action Research to Alleviate Speaking Anxiety of Prospective EFL Teachers
Keywords: Other Fields of Education; Alan Eğitimleri